Convolvulus pluricaulis extract can modulate synaptic plasticity in rat brain hippocampus. Issue 8 (22nd May 2020) - Das, Rishi; Sengupta, Tathagata; Roy, Shubhrajit; Chattarji, Sumantra; Ray, Jharna
Abstract : The memory-boosting property of Indian traditional herb, Convolvulus pluricaulis, has been documented in literature; however, its effect on synaptic plasticity has not yet been reported. Two important forms of synaptic plasticity known to be involved in the processes of memory formation are long-term potentiation (LTP) and long-term depression (LTD). In the present study, the effect of C. pluricaulis plant extract on LTP and LTD were evaluated. The adult male Wistar rats were fed orally with 250, 500 and 1000 mg/kg of this extract for 4 weeks and the effect was determined on LTP and LTD in the Schaffer collaterals of the hippocampal cornu ammonis region CA1. We found that the 500 mg/kg dose of the extract could significantly enhance LTP compared to the vehicle treated ones. Moreover, the same dose could also reduce LTD while used in a separate set of animals. Also, a fresh group of animals treated with the effective dose (500 mg/kg) of plant extract were examined for memory retention in two behavioral platforms namely, contextual fear conditioning (CFC) and novel object recognition test (NORT). Increased fear response to the conditioned stimulus and enhanced recognition of objects were observed in CFC and NORT, respectively, both indicating strengthening of memory. Following up, ex-vivo electrophysiology experiments were performed with the active single molecule scopoletin, present in C. pluricaulis extract and similar patterns in synaptic plasticity changes were obtained. These findings suggest that prolonged treatment of C . pluricaulis extract, at a specific dose in healthy animals, can augment memory functions by modulating hippocampal plasticity.